Evaluation of sponge gourd (Luffa cylindrica) hybrids for yieldcontributing traits - Aishwarya Sharma; B Singh; YK Sharma; Uadal Singh; A Choudhary (Current Horticulture, 2025)
The study was undertaken to find the performance of 28 hybrids of sponge gourd [Luffa cylindrica (L.) Roem.] through diallel mating design excluding reciprocals at Rajasthan Agricultural Research Institute, Durgapura, Jaipur, Rajasthan. Observations were recorded on days to initiation of first female flower, days to 50% flowering, number of nodes at which first female flowers appear, number of primary branches/vine, vine length at final harvesting, days to first fruit harvesting, fruit size, average fruit weight, average fruit yield (g/plant), average fruit yield (kg/plot), total fruit yield (q/ha.). Among the hybrids, ‘VRSG-17-27 × Pusa Chikni’, ‘VRSG-17-27 × Kashi Shreya’, ‘Kashi Shreya × PSG-40’, ‘Kashi Shreya × Pusa Chikni’, ‘VRSG-17-4 × VRSG-17-27 and ‘VRSG-17-27 × PSG-40’excelled n number of nodes at which first female flower appears, days to initiation of first female flowers appear and fruit yield. Thus, first generation hybrids can be well-utilized for exploiting hybrid vigor to achieve higher yield with improved quality.